白术内酯I在制备用于抑制乳腺癌肺转移药物中的应用 (2025)
本发明公开了白术内酯I在制备用于抑制乳腺癌肺转移药物中的应用。本发明提供了白术内酯I的一种新用途，其可降低乳腺癌细胞的肺部转移能力。当白术内酯I作为药物使用时，乳腺癌荷瘤小鼠实验表明，白术内酯I能够显著抑制乳腺癌肺转移的发生发展，并且对小鼠体重无显著影响，具有较高的安全性。因此，白术内酯I有望开发成新的抑制乳腺癌肺转移的药物。 The invention discloses application of atractylenolide I in preparation of a medicine for inhibiting lung metastasis of breast cancer. The invention provides a new application of atractylenolide I. The atractylenolide I can reduce the lung metastasis capability of breast cancer cells. When the atractylenolide I is used as a medicine, a breast cancer tumor-bearing mouse experiment shows that the atractylenolide I can obviously inhibit the occurrence and development of breast cancer lung metastasis, has no obvious influence on the weight of a mouse, and has relatively high safety. Therefore, atractylenolide I is expected to be developed into a novel medicine for inhibiting lung metastasis of breast cancer.